HADIS DALAM BUDAYA INDONESIA ABAD XVII-XVIII: KAJIAN ATAS PEMIKIRAN ABD RAUF SINKEL - Rahmah, Wahyuni Shifatur (El-Mu'Jam. Jurnal Kajian Al Qur'an dan Al-Hadis, 2024)
Special attention to the study of the hadith or sunnah of the Prophet as the second source of Islamic law, led Al-Sinkili to a greater appreciation of the meaning of sharia and Sufism. This can be found in references to works in the form of tafsir, fiqh, and Sufism in the form of hadith histories. This research uses qualitative methods and is descriptive analysis, namely by systematically describing and describing discussion materials obtained from various sources, both primary and secondary sources which are then analyzed to obtain research results. The results of this research, especially regarding the development of hadith studies in Indonesia in the XVII-XVIII centuries, provide an illustration that hadith at that time had not yet developed into a separate discipline, because the study of hadith was new on a practical plane, not yet theoretically structured. Although there has been Al-Sinkili's work on hadith, namely; Syarah Latif 'ala Arba'in Hadisan li Imam an-Nawawi and al-Mawa'iz al-Badi'ah, but access to these works is still very difficult.